FORMULASI GRANUL INSTAN EKSTRAK HERBA PEGAGAN (Centella asiatica) DAN ANALISIS ASIATIKOSIDA - - Prasetyorini; Bina Lohitasari; Ahmad Amirudin (EKOLOGIA, 2012)
The research was conducted in the month from February until April 2011 in the laboratory of Pharmacy Faculty of Mathematics and Natural Sciences, University Pakuan. The research objective is to make a health drink formulation of herbs gotu kola extract and determine the form of instant granules asiatikosida content. Herb gotu kola is used in this study is the collection BALITRO. In this study of instant granules prepared by wet granulation method and made three formulas are: FI (formula without essence), F II (formula with caramel essence, and F III (formula with mango essence.) Asiatikosida analysis performed on dry ekstrakt by TLC method the scanner. the results showed all formulas have the instant granule flow rate and good Sagat compressibility, organoleptic tests (smell and color), which are the F III, asiotikosida content showed a decrease during processing. Gynecology asiatikosida ekstrakt dry is 1.75% (4.375 mg asiatikosida) , instant granules FI of 0.46% (0.052 mg asiatikosida), F II by 0.68% (0.072 mg asiatikosida), and F III amounting to 0.48% (0.056 mg asiatikosida). Rf value on testing asiatikosida in extracts obtained 0.81 with a standard 0.80. Rf value on testing for FI 0.28 instant granules; FII 0.28, and F III 0.29, the standard used for Rf value of 0.28Kata kunci : ekstrak herba pegagan, granul instan, asiatikosida